ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEK PEMBANGUNAN MANUSIA (IPM) KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT TAHUN 2006-2010 - DWI HERIYANTO, B61109049 (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACTBylooking at the real condi t ionsof Kal imantan Barat humanDeveloping Index in periode 2006-2010, that has 68,12 percent ofHDI’s average, that also bring Kal imantan Barat to order on 28t hin1009 and 2010. So i t ’s neccesarry to know wha thatcauseKal imantan Barat is toolow.The purpose of thie reaserch is f inding roles between HDIrariables in regency/ci ty of Kal imantan Barat , that representated byindicator of heal t , educat ion and income per capi ta, that ’s thefunct ion of economi indicator, f inancial indicator of humandeveloping, poverty indicators, educat ion indicators and heal thindicator.The resul ts showed that the increase in human developmentRegency / Ci ty in the province of West Kal imantan is inf luenced bya variety of indicators forming the HDI i tsel f , wi th di f ferentcontribut ion for each model studies.In general , the growth of human development achieved by theProvince of West Kal imantan during the years 2006-2010 haveshown that the development of qui te volat i le, visible reduct ion ofthe value of the reducher short fal l (RS) which is somet imesincreased and decreased, respect ively as fol lows 2,58; 1.37; 1.96;1.94; The f igure 1.17 shows that the development of HDI in WestKal imantan is not stable and i t is necessary for improvement .The variables that af fect the dominant cause of the low HDIin District / Ci ty of West Kal imantan Province is the heal thvariable, the indicator AHH very low compared to other regencies /ci t ies.Keywords: l i fe expectancy, the average length school ,Literacy and adjusted expendi ture per capita.